Synthesis of a phenylboronic acid-functionalized thermosensitive block copolymer and its application in separation and purification of vicinal-diol-containing compounds. Issue 85 (30th August 2016) - Wang, Yun; Li, Yuanyuan; Han, Juan; Tang, Xu; Ni, Liang; Hu, Xiaowei; Wang, Lei
Abstract : Phenylboronic acid-functionalized PEO20 PPO60 PEO20 was synthesized and used to separate ortho -hydroxyl compounds as the collector in an aqueous two-phase flotation system. Abstract : A phenylboronic acid-functionalized amphiphilic thermosensitive block copolymer was prepared by taking PEO20 PPO60 PEO20 as the template and a detailed study of its performance in downstream separation processes was presented. Alizarin red was used as the model compound to study the feasibility of using an affinity adsorption system and aqueous two-phase flotation system based on the phenylboronic acid-functionalized PEO20 PPO60 PEO20 for the separation and purification of ortho -hydroxyl compounds. The optimized conditions of the affinity adsorption experiment were: 2% phenylboronic acid-functionalized PEO20 PPO60 PEO20, 0.3 mg alizarin red, 40% K2 HPO4 and 4 h adsorption time. The affinity adsorption rate of alizarin red reached 98% under such conditions. In addition, a flotation recovery of alizarin red of 97% was obtained under the optimal conditions of aqueous two-phase flotation: 0.3 g of collector, 12 g K2 HPO4, 0.6 mg alizarin red, 15 mL min −1 nitrogen flow rate and 40 min flotation time. Both methods are capable of separating alizarin red, suggesting their broad application prospect in downstream separation engineering of vicinal-diol-containing compounds.